2020
DOI: 10.21203/rs.2.18901/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

G-Protein-Coupled Estrogen Receptor Activation Upregulates Interleukin-1 Receptor Antagonist in the Hippocampus after Global Cerebral Ischemia: Implications for Neuronal Self Defense

Abstract: Background: G-protein-Coupled Estrogen Receptor (GPER/GPR30) is a novel membrane-associated estrogen receptor that can induce rapid kinase signaling in various cells. Activation of GPER can prevent hippocampal neuronal cell death following transient global cerebral ischemia (GCI), although the mechanisms remain unclear. In the current study, we sought to address whether GPER activation exerts potent anti-inflammatory effects in the rat hippocampus after GCI as a potential mechanism to limit neuronal cell death… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A recently published study shows that GPER activation upregulates interleukin-1 receptor antagonism in the hippocampus after GCI and thus limits ischemic cell death [143]. Importantly, this study suggests that GPER preserves cognitive function following GCI via enhancing the anti-inflammatory defense mechanism of neurons by upregulating interleukin-1β receptor antagonist (IL1RA) [143].…”
Section: Recapitulating Human Female Reproductive Phases In Laboratormentioning
confidence: 78%
See 1 more Smart Citation
“…A recently published study shows that GPER activation upregulates interleukin-1 receptor antagonism in the hippocampus after GCI and thus limits ischemic cell death [143]. Importantly, this study suggests that GPER preserves cognitive function following GCI via enhancing the anti-inflammatory defense mechanism of neurons by upregulating interleukin-1β receptor antagonist (IL1RA) [143].…”
Section: Recapitulating Human Female Reproductive Phases In Laboratormentioning
confidence: 78%
“…Subsequently studies reported that GPER activation via G1 administration could rapidly activate PI3K-Akt and MEK-ERK, which are rapid kinase signaling pathways in the hippocampus, and exert strong neuroprotection against global cerebral ischemia (GCI) [71,137,142]. A recently published study shows that GPER activation upregulates interleukin-1 receptor antagonism in the hippocampus after GCI and thus limits ischemic cell death [143]. Importantly, this study suggests that GPER preserves cognitive function following GCI via enhancing the anti-inflammatory defense mechanism of neurons by upregulating interleukin-1β receptor antagonist (IL1RA) [143].…”
Section: Recapitulating Human Female Reproductive Phases In Laboratormentioning
confidence: 99%
“…Depending on which receptor the hormones bind to, different cascades with different kinetics can be initiated [ 41 ]. Although there is little literature on the estrogen receptors (ERalpha, ERbeta, and GPR30) for cancer and in connection with NLRP3, their impact on NLRC4 and AIM2 is not described yet [ 42 , 43 ]. In addition, the concentration and temporal administration of both hormones might also influence the detected effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is now recognised to have an inflammatory component to its pathophysiology (Drummond et al, 2019) with inflammasomes (Pasqua et al, 2018) and T cells (Dinh et al, 2021; Guzik et al, 2007) playing significant roles. Indeed, GPER has potent anti‐inflammatory effects in the circulation (Sharma et al, 2020) and BP‐regulating organs such as the kidneys (Kurt et al, 2016) and brain (Bai et al, 2020). Although activation of GPER has been shown to have anti‐inflammatory effects on T cells (Brunsing et al, 2013), the antihypertensive effects of GPER activation do not appear to involve an action on T cells in aldosterone‐induced hypertension (Dinh et al, 2021).…”
Section: Gper and Cardiovascular Diseasementioning
confidence: 99%
“…Hence, although there remains to be a great deal of further work to understand these sex‐specific findings, it is plausible that men might benefit from GPER antagonists, whereas postmenopausal women might gain protection from GPER agonists administered for the acute treatment of ischaemic stroke. Neuroprotective effects of GPER could involve antiapoptotic actions (Bai et al, 2020; Broughton et al, 2014; Han et al, 2019; Rzemieniec et al, 2015; Tang et al, 2014).…”
Section: Gper and Outcomes Of Cardiovascular Eventsmentioning
confidence: 99%